INFLUENCE OF TECHNOLOGY LEADERSHIP AND USE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN SCHOOLS: ONE ANALYSIS - Mohd Helmee Firdaus Salehudin, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
eadership has a positive relationship in the performance of an organization withsignificant impact in influencing individuals and organizations achieve effectiveness. In linewith the implementation and integration of the use of information and communicationtechnology (ICT) in schools, school leadership role very important in implementing the agendathe Ministry of education (MOE) to answer the development of ICT in the globalization.Nevertheless, analysis of the findings of several studies have shown the use of computers inVolume: 1 Issues: 2 [December, 2016] pp.17-23]International Journal of Education, Psychology and CounselingeISSN: 0128-164XJournal homepage: www.ijepc.com18schools Malaysia still stood at a low level and medium level achievement in vision andleadership in the implementation of ICT in schools. Therefore, the approach to technologyleadership are needed to establish the effectiveness of ICT integration in school. Approach toleadership competency ICT technology to create school leaders self in order to lead effectivelyand provide their school to face the future.